In vitro evaluation of the antimicrobial activity of nanosilver-mineral trioxide aggregate against frequent anaerobic oral pathogens by a membrane-enclosed immersion test - Abbas Bahador (Biomedical Journal, 2015)
Background: Nanoparticles of silver (NanoAg) have been shown to control the growth of bacteria, but application of NanoAg in endodontics has not been evaluated. This in vitro study evaluates the antimicrobial activity of NanoAg to enhance the inhibitory effects of mineral trioxide aggregate (MTA). Methods: The antibacterial activities of NanoAg and NanoAg-MTA against four types of anaerobic pathogens were tested in vitro using (1) agar diffusion test (ADT) and (2) a newly devised membrane-enclosed immersion test (MEIT). Results: Both NanoAg and NanoAg-MTA inhibited the growth of all four test bacteria at 25 ppm concentration. MEIT analysis consistently showed that NanoAg enhanced the antimicrobial activity of MTA significantly, and the bacterial susceptibility to lower concentrations of NanoAg varied depending on the type of bacteria. Overall, NanoAg-MTA showed significant inhibitory effect which was time and dose dependent. Conclusions: Our data support that NanoAg can serve as an excellent MTA additive against anaerobic endodontic-periodontal pathogens with clinical applications for infection control in endodontics.